BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN KEDISIPLINAN PEMAKAIAN ALAT PELINDUNG TELINGA DI BAGIAN WEAVING PT. PRIMATEXCO INDONESIA KABUPATEN BATANG - Dewi Nugraheni Restu Mastuti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
Doing least the job can give accident risk for the subject, but the risk of accident can be overcame with requires every employee to obey all the role in the company that connect with savety and job product. This study to determine what factorsare related  with use of APT Weaving PT. Primatexco Batang Ltd. To know education level connect, long of work, socialization about APT used, punise subject  not  wear  APT,    be  afraid  to  supervisor,  APT  condition  with  discipline  use  APT  at  part  of weaving  of  Primatexco,  Ltd  Batang  Regency. This  study is  an observational research with cross sectional approach. This research do with observation and APT used at the work area. Statistics test with univariate analysis and bivariate analysis to determine several factors related to discipline APT used. The results after used chi square test,to known that factors not connect education level, long of work, socialization about, punishment, fear of supervisors to discipline the used of APT obtained value of X ² table (3.481)> calculated  value X ² (0.473,  0.777,  0.4796,  0.453, 0.473). And factors related to the condition of the APT with a value of X ² table (3.481)> X ² calculated value (0.035). Concluded that there was no association factor is the level of education, long work,socialization of APT,  punishment,  fear  of  supervisors to discipline the  used of APT and factors  related  to the condition of APT. Keywords: Personal Protective Equipment Ear, Discipline